Response of sunflower (Helianthus annuus) to phosphorus, sulphur, micronutrients and humic acid under irrigated condition on red sandy-loam soil - VASUDEVAN, S N; VIRUPAKSHAPPA, K; VENUGOPAL, N; BHASKAR, S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during rainy season of 1990Â  Â to study the response of sunflower (Helianthus annuusL.) genotypes (hybrid 'KBSH 1', inbred line 'HA 234 B' and open-pollinated variety 'Morden') to phosphorus, sulphur,micronutrients (zinc and boron) and humic acid along with recommended doses of N, P and K @39.6 and 50.4 kg/harespectively. Both nutrients and genotypes significantly influenced the leaf - area index, seed yield, filled seeds/capitulum, seed filling (%), volume weight, achene and kernel-oil content. The interaction effects were found non-significant. 'KBSH 1 ' gave the highest yield (3 840 kg/ha), being 58 and 94% higher than that of 'Morden' and 'HA 234 B' (2430 and 1 980 kg/ ha respectively). The highest yield (3 070 kg/ha) was recorded with the combination of all nutrients, which was on a parwith the recommended fertilizer + borax dusting @ 2 kg/ha (2 910 kg/ha) and significantly superior to all the other treatments. The yield increased owing to improvement in yield components, viz filled seeds/head (1 066), seed filling (%) (86.2), 1 000 - seed weight (63.9 g) and leaf-area index (3.81). These treatments also influenced the oil (50.3%) and protein (21.9%) contents compared with the control. The nutrients increased the seed-quality parameters such as higher germination (%) after accelerated ageing (61.8%), higher speed of germination (22.2), higher shoot (23.4 cm) and root lengths (20.4 cm), higher vigour index (3 947) and seedling-growth rate (25.1 cm) compared with the control.